Live cell optical super-resolution microscopy of dystroglycan mutants as a model for dystroglycanopathies in multiple cell lines - Sciandra, Francesca; Bozzi, Manuela; Witt, Alina; Goffing, Paul; Covaceuszach, Sonia; Blaess, Sandra; Cassetta, Alberto; Bigotti, Maria Giulia; Huser, Thomas; Brancaccio, Andrea; Hübner, Wolfgang (Frontiers in Molecular Biosciences, 2025)
IntroductionDystroglycan (DG) is an adhesion complex comprising two subunits, α-DG and β-DG, which interact non-covalently at the plasma membrane. As a component of the dystrophin-glycoprotein complex DGC, DG plays a crucial role in linking the cytoskeleton to the surrounding basement membranes. Rare primary point mutations in the DAG1 gene have been identified in patients with various forms of neuromuscular dystrophy, ranging in phenotype from mild to severe.MethodsTo gain a deeper understanding of the molecular mechanisms underlying these pathologies, we have designed a series of chimeric GFP-tagged full-length α/β-DG constructs and expressed them in three different cell lines (U-2OS, HEK-293T and C2C12). Wild-type DG constructs were compared to their counterparts carrying pathologic missense mutations previously described in patients, namely, L84F, T190M and C667F and with the mutant I591D, i.e., the topological equivalent of V567D identified in zebrafish.ResultsLive super-resolution fluorescence microscopy showed that the C667F mutant is retained within the ER/Golgi while the T190M and wild-type proteins are correctly localized to the plasma membrane in all 3 cell lines. The L84F mutant exhibits a delay in trafficking to the plasma membrane in two of the cell lines, while localizing strongly at the plasma membrane in the high-expression HEK-293T cells. Similarly, the I591D mutant accumulated at the plasma membrane in the HEK-293T cells, in contrast to the clear retention in the endoplasmic reticulum/Golgi apparatus observed in U-2OS and C2C12 cells.DiscussionOur data demonstrate the importance of using a range of different cell lines for a comprehensive study of DG mutants or variants by live cell optical super-resolution microscopy.